A case report of multiple bilateral dens invaginatus in maxillary anteriors - Shin Hye Chung; You-Jeong Hwang; Sung-Yeop You; Young-Hye Hwang; Soram Oh (Restorative Dentistry & Endodontics)
The present report presents a case of dens invaginatus (DI) in a patient with 4 maxillary incisors. A 24-year-old female complained of swelling of the maxillary left anterior region and discoloration of the maxillary left anterior tooth. The maxillary left lateral incisor (tooth #22) showed pulp necrosis and a chronic apical abscess, and a periapical X-ray demonstrated DI on bilateral maxillary central and lateral incisors. All teeth responded to a vitality test, except tooth #22. The anatomic form of tooth #22 was similar to that of tooth #12, and both teeth had lingual pits. In addition, panoramic and periapical X-rays demonstrated root canal calcification, such as pulp stones, in the maxillary canines, first and second premolars, and the mandibular incisors, canines, and first premolars bilaterally. The patient underwent root canal treatment of tooth #22 and non-vital tooth bleaching. After a temporary filling material was removed, the invaginated mass was removed using ultrasonic tips under an operating microscope. The working length was established, and the root canal was enlarged up to #50 apical size and obturated with gutta-percha and AH 26 sealer using the continuous wave of condensation technique. Finally, non-vital bleaching was performed, and the access cavity was filled with composite resin.